"School's a Lie": Toward Critical Race Intersectional Pedagogy for Youth Intellectual Activism in Policy Partnerships. Issue 1 (January 2022) - Sheth, Manali J.; Salisbury, Jason D.
Equity-oriented school improvement driven by neoliberal policies focuses attention on a narrow range of inequities. Such policies fail to achieve substantive transformations that address educational constraints experienced by multiply-marginalized youth of color. We engage a critical race and intersectional feminist examination of our pedagogy in a youth voice initiative designed to facilitate multiply-marginalized youth of color participation in district policy partnership. Our analysis presents practices that were consequential for supporting youth intellectual activism in policy conversations. We propose a model for critical race intersectional pedagogy that relates these practices and underlying ideological principles to supporting expansive transformative policy partnerships.